Prenatal diagnosis of familial transmission of 17q12 microduplication associated with no apparent phenotypic abnormality - Chih-Ping Chen; Chung-Hu Fu; Yi-Hui Lin; Schu-Rern Chern; Peih-Shan Wu; Yen-Ni Chen; Shin-Wen Chen; Wayseen Wang (Elsevier, 2016)
Objective: We present prenatal diagnosis of familial transmission of 17q12 duplication associated with no apparent phenotypic abnormality. Case Report: A 36-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Cytogenetic analysis revealed a karyotype of 46,XY. Array comparative genomic hybridization of uncultured amniocytes revealed a 1.42-Mb duplication of 17q12 or arr 17q12 (34,822,465-36,243,365) × 3 encompassing 12 Online Mendelian Inheritance in Man (OMIM) genes including LHX1, ACACA, and HNF1B. Array comparative genomic hybridization analysis of parental bloods revealed no genomic imbalance in the mother, and a result of arr 17q12 (34,611,377-36,248,889) × 2.9 encompassing 16 OMIM genes, including LHX1, ACACA, and HNF1B, in the 29-year-old phenotypically normal father. Prenatal ultrasound findings were unremarkable. The parents elected to continue the pregnancy. At 37 weeks of gestation, a 2789-g normal male baby was delivered uneventfully. When examined at the age of 7 months, the neonate was as phenotypically normal as his father. Conclusion: The 17q12 microduplication may present with variable phenotypes including no apparent phenotypic abnormality in familial cases. However, neuropsychiatry assessment and monitoring should be warranted in childhood and through adulthood under such a circumstance.